Commuting, wages and bargaining power - Peter Rupert; Elena G. F. Stancanelli; Etienne Wasmer (Institute for the Study of Labor (IZA), 2009)
A search model of the labor market is augmented to include commuting time to work. The theory posits that wages are positively related to commute distance, by a factor itself depending negatively on the bargaining power of workers. Since not all combinations of distance and wages are accepted, there is non-random selection of accepted job offers. We build on these ingredients to explore in the data the relationship between wages and commute time. We find that neglecting to account for this selection will bias downward the wage impact of commuting, and marginally affect the coefficients on education, age and gender. The correlation between the residuals of the selectivity equation and the distance equation is -0.70, showing the large impact of commute time on job acceptance decisions. We also use the theory to calculate the bargaining power of workers which largely varies depending on demographic groups: it appears to be much larger for men than that for women and that the bargaining power of women with young children is essentially zero.
urn:nbn:de:101:1-20091105819
Keywords: J3; J6; R2; 330; Commuting; search model; simultaneous equations; Lohnbildung; Berufsverkehr; Arbeitsuche; Lohnverhandlungen; Verhandlungsmacht; Theorie; Simultanes Gleichungssystem; Schätzung; EU-Staaten